Bridging cultural categories of consumption through indeterminacy: A consumer culture perspective on the rise of African Pentecostal-Charismatic Christianity. (February 2019) - Appau, Samuelson; Awaworyi Churchill, Sefa
Postmodern discourse challenges dichotomous cultural categories such as male/female, past/present and consumer/producer; it rather venerates the complexity, fusion, and diffusion of cultural categories. This ideology suggests that indeterminate or fluid cultural categories liberate consumer culture discourse availing it to varying consumer needs. African Pentecostal-Charismatic Christianity advances such a postmodernist discourse that recognizes and bridges indeterminate physical, temporal, moral, and symbolic cultural categories of consumption. This is achieved through two processes: convergence and divergence. Fluid and capable of meandering rigid cultural categories and structures, African Pentecostal-Charismatic Christianity theology is attractive to a broader audience of consumers because it appeals to a wider array of consumers' demands/desires. This article thus advances that African Pentecostal-Charismatic Christianity continues to grow due its ability to fluidly adapt its postmodern theology to the variegated consumption needs and identity projects of the postcolonial African consumer.